Spectroscopic study of the effects of dissolved organic matter compositional changes on availability of cadmium in paddy soil under different water management practices - Li, Zhongwu; Huang, Mei; Luo, Ninglin; Wen, Jiajun; Deng, Chuxiong; Yang, Ren (Chemosphere (Oxford), 2019)
It is well established that water management can influence the availability of Cd in paddy soil but the role of dissolved organic matter (DOM) characteristics in this process is still unclear. Here, we measured and compared the DOM quantity and quality between flooded and wetted treatments by spectroscopic and chemometric analysis and applied correlation analysis to relate DOM characteristics with availability concentrations of Cd. Ultraviolet–visible showed that aromaticity and hydrophobicity of DOM significantly decreased with time in wetted paddy soil (p < 0.05) but had no significant difference in flooded paddy soil (p > 0.05). According the results from two-dimensional correlation spectroscopy analytical method, humic- and protein-like substances had fast response during cultivation process. Two humic-like substances (C1, C2) and two protein-like substances (C3, C4) were identified from paddy soil-derived DOM by combining emission and excitation matrix spectroscopy with parallel factor. Compared to component C1, C3, and C4, component C2 has stronger aromaticity and hydrophobicity and higher molecular size (665–1000 Da). Its proportion declined markedly during the wetting periods but increased slightly during flooding. Pearson correlation analysis illustrated that flooding was more helpful in immobilizing Cd than wetting due to the aromatic, hydrophobic, and high molecular weight constituents remained in flooded treatments and the substantial decomposition of component C2 in wetted treatments. These results suggested that spectroscopic and chemometric methods are helping to further explain the impacts of DOM quality on Cd availability under different water management practices. [Display omitted] •Spectroscopic and chemometric analysis methods were used in this paper.•Flooding is more conducive to preserve aromatic and hydrophobic substances.•After 60d, available Cd in wet soil is 2.55 mg kg−1 more than that in flooded soil.•Cd availability is strongly related to DOM quality during flooding and wetting.•Wetting mobilizes Cd because aromaticity, hydrophobicity and molecular weight fall.